2(n+9)=6(n-5)+8

Simple and best practice solution for 2(n+9)=6(n-5)+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(n+9)=6(n-5)+8 equation:



2(n+9)=6(n-5)+8
We move all terms to the left:
2(n+9)-(6(n-5)+8)=0
We multiply parentheses
2n-(6(n-5)+8)+18=0
We calculate terms in parentheses: -(6(n-5)+8), so:
6(n-5)+8
We multiply parentheses
6n-30+8
We add all the numbers together, and all the variables
6n-22
Back to the equation:
-(6n-22)
We get rid of parentheses
2n-6n+22+18=0
We add all the numbers together, and all the variables
-4n+40=0
We move all terms containing n to the left, all other terms to the right
-4n=-40
n=-40/-4
n=+10

See similar equations:

| 10+12y=7 | | x-6=2x13 | | −10(x+4)+203=43 | | −10(x+4)+203=31+12 | | 8x+1=153 | | 7x+1=153 | | 2x-20(x+15)=180 | | 2x-3(x-1)=4+5x | | 1/3x+2/5=1/15-2x | | 2d+1/6=6{1/3d+1 | | 16x+13=24 | | 13x+25=115−2x | | 16x+10=24 | | 2=7t+4 | | 3(t-2)+3=3(2t-5) | | 2a+14-4a-7+8a=16-3+15=28 | | x+5/2=6-x+6/5 | | 9x+3=56 | | 10+8=-3(2x-6) | | 6(y+2)=-14 | | 5(2x+5)=-38+33 | | x+2/2=4-x+1/5 | | 6x+30=x+15 | | 8(n+6)=7n | | 9+5n=7(6n-4) | | -6(9+2f)=f=9 | | -8(t+1)-1t-11=9(t+4)+17 | | {3x+4}{2}=9.5 | | -8(t+1)-t-11=9(t+4)+17 | | -6(9+2f)f=9 | | 25x–3×5x+2=0 | | 9-6r-3r=4 |

Equations solver categories